Analisis Kontribusi Keuntungan Atas Produk Produk Pada Usaha Moulding Keramajaya Di Tenggarong (Penerapan Linear Programming Metode Simpleks) - Abdul Gafur; Erwinsyah Erwinsyah; Syahruddin S (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
The purpose of this study was to determine whether the production volume of the Keramajaya Muolding Business in Tenggarong was at the optimal point to generate maximum profit. The analytical tool used is the simplex method. The primary data used is the production costs incurred in carrying out product manufacturing activities in 2019. The results of the simplex method analysis show that during 2019 the Keramajaya Molding Business in Tenggarong generated gross sales of Rp. 282.850.000 (442 units of product) consisting of 182 units of doors, 126 windows and 134 units of frame with a net profit of Rp. 36,110,000. The results of the analysis of the calculation of the simplex method obtained optimal gross sales of Rp. 220,000,000 (220 units all doors) with a net profit of Rp. 29,700,000. From these two comparisons, it can be concluded that the production of the Keramajaya Molding Business in Tenggarong in 2019 was optimal because it generated profits above Rp. 29,700,000. So that the first hypothesis in the study is accepted because it is proven true.